HUBUNGAN KUALITAS TIDUR DAN INDEKS MASSATUBUH TERHADAP TINGKAT KONTROL ASMA DI RSUD KOTA BEKASI TAHUN 2019 - Winda Hayati Ginting (2019)
Asthma is an obstruction of the airway caused by several factors. One of the triggers for asthma is sleep quality and body mass index. Poor sleep quality is where one has difficulty starting and maintaining sleep. Whereas body mass index is a simple way to find out nutritional status in adults. Poor sleep quality accompanied by uncontrolled BMI will make the patient susceptible to inflammation so it is prone to recurrence of asthma. This study aims to determine the relationship of sleep quality and body mass index with the level of asthma control in adult asthma patients in Bekasi City Hospital in 2019 by using the asthma control test questionnaire, Pittsburgh Sleep Quality and medical records. This research is an observational analytic study with cross sectional design and Chi-Square data analysis. The results of a study of 42 samples taken using the consecutive sampling tecnic. A significant relationship was found between the level of asthma control and sleep quality (p = 0.021) and a non-significant relationship was found between the level of asthma control and body mass index (p = 0.958)